Explicit decomposition of a rational prime in a cubic field - Saban Alaca; Blair K. Spearman; Kenneth S. Williams (International Journal of Mathematics and Mathematical Sciences)
We give the explicit decomposition of the principal ideal 〈p〉 (p prime) in a cubic field.